CD38 deficiency protects the retina from ischaemia/reperfusion injury partly via suppression of TLR4/MyD88/NF-κB signalling. (June 2022) - Chen, Guiping; Yan, Feng; Wei, Wei; Wang, Feifei; Wang, Zhiruo; Nie, Jiahe; Jin, Ming; Pang, Yulian; Qin, Mengqi; Wang, Lingfang; Zhang, Xu
Abstract: Purpose: This study aimed to explore cellular localisation of CD38 in the retina and evaluate the role and potential mechanism of CD38 deficiency in retinal ischaemia/reperfusion (I/R) injury. Methods: Six-to eight-week-old male CD38 knockout (KO) and wild-type mice in C57BL/6 background were used. Immunostaining was performed to determine the cellular localisation of CD38 in the retina. Haematoxylin and eosin staining and immunostaining of Brn3a were used to evaluate the retinal I/R injury. Western blotting was performed to detect toll-like receptor 4 (TLR4), myeloid differentiation primary response 88 (MyD88), p-p65, ionised calcium-binding adapter molecule 1, Sirtuin1 (Sirt1), Ac-p65, and pro-inflammatory cytokines protein expression. Results: CD38 was highly expressed in mouse retinal microglia and astrocytes/Müller cells. CD38 deficiency reduced I/R-induced retinal damage and retinal ganglion cell death. Following retinal I/R injury, TLR4, MyD88, nuclear factor-κB p-p65 (NF-κB p-p65), pro-inflammatory cytokines and CD38 protein levels were also upregulated. After I/R injury, retinal inflammation factors IL-1β, IL-6, and TNF-α mRNA and protein levels were increased. IL-1β, IL-6, and TNF-α were reduced in CD38 KO mice after I/R injury. Retinal I/R injury induced the activation of microglia, but this effect was also suppressed by KO of CD38. Additionally, retinal I/R induced a significant increase in Ac-p65 protein levels and decrease in Sirt1 protein levels, while this effect was greatly attenuated by KO of CD38. Conclusion: CD38 deficiency protects the retina from I/R injury by suppressing microglial activation partly via activating Sirt1-mediated suppression of TLR4/MyD88/NF-κB signalling. Highlights: CD38 was highly expressed in mouse retinal microglia and astrocytes/Müller cells. CD38 deficiency reduced ischaemia/reperfusion (I/R)-induced retinal damage and retinal ganglion cell death. TLR4/MyD88/NF-κB signalling participates in retinal I/R injury. CD38 deficiency suppressed I/R-induced the TLR4/MyD88/NF-κB signalling pathway by upregulating Sirt1.